Deciphering Key microRNA Regulated Pathways in Tissue-Engineered Blood Vessels: Implications for Vascular Scaffold Production - Rodrigues, Lenize da Silva [UNESP]; Felix, Tainara Francini [UNESP]; Minutentag, Iael Weissberg [UNESP]; Reis, Patricia Pintor [UNESP]; Bertanha, Matheus [UNESP] (MDPI, 2024)
MicroRNAs (miRNAs) are non-coding RNAs involved in the regulation of gene expression associated with cell differentiation, proliferation, adhesion, and important biological functions such as inflammation. miRNAs play roles associated with the pathogenesis of chronic degenerative disorders including cardiovascular diseases. Understanding the influence of miRNAs and their target genes can effectively streamline the identification of key biologically active pathways that are important in the development of vascular grafts through the tissue engineering of blood vessels. To determine miRNA expression levels and identify miRNA target genes and pathways with biological roles in scaffolds that have been repopulated with adipose-derived stem cells (ASCs) generated through tissue engineering for the construction of blood vessels. miRNA quantification assays were performed in triplicate to determine miRNA expression in a total of 20 samples: five controls (natural inferior vena cava), five scaffolds recellularized with ASCs and differentiated into the endothelium (luminal layer), five samples of complete scaffolds seeded with ASCs differentiated into the endothelium (luminal layer) and smooth muscle (extraluminal layer), and five samples of ASC without cell differentiation. Several differentially expressed miRNAs were identified and predicted to modulate target genes with roles in key pathways associated with angiogenesis, vascular system control, and endothelial and smooth muscle regulation, including migration, proliferation, and growth. These findings underscore the involvement of these pathways in the regulatory mechanisms that are essential for vascular scaffold production through tissue engineering. Our research contributes to the knowledge of miRNA-regulated mechanisms, which may impact the design of vascular substitutes, and provide valuable insights for enhancing clinical practice. The molecular pathways regulated by miRNAs in tissue engineering of blood vessels (TEBV) allowed us to elucidate the main phenomena involved in cellular differentiation to constitute a blood vessel, with the main pathways being essential for angiogenesis, cellular differentiation, and differentiation into vascular smooth muscle.
Keywords: peripheral arterial disease; stem cells; tissue transplant-based therapy